Kontinuitas Ideologi Developmentalisme dalam Pemberitaan PSN PIK 2 di Detik.com - Sultan Rafly Dharmawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the continuity of the ideology of developmentalism in post-Reformasi Indonesian online media discourse, using the case of the coverage of the Pantai Indah Kapuk 2 (PIK 2) National Strategic Project (PSN) on Detik.com. Developmentalist thinking has never completely disappeared since the end of the New Order era to the present day (Adiprasetio, 2025; Romano, 1999), Therefore, this study empirically tests this thesis using Fairclough’s (1995) three-dimensional model of Critical Discourse Analysis (CDA), Gramsci’s (1971) theory of hegemony, and the media political economy frameworks of Tapsell (2017) and Hadiz & Robison (2005). Six news articles from Detik.com published between August 2023 and December 2024 were analysed qualitatively. The findings reveal three patterns of ideological continuity: (1) the construction of the PSN as an indisputable national interest that replicates the logic of the ‘Pancasila Press’; (2) the delegitimisation of affected citizens as obstacles to progress, which echoes the ‘threat to stability’ mechanism of the New Order era; and (3) a shift in hegemonic mechanisms from direct state repression towards structural bias in media conglomerate ownership. This study argues that within Indonesia’s post-Reform media oligarchy ecosystem (Tapsell, 2017), developmentalist hegemony operates through the internalisation of the boundaries of the produced discourse. A mechanism is at work that, in its effects, is equivalent to New Order-era censorship but leaves no visible traces of coercion.